Loop connectors in dentogenic diastema - Sanjna Nayar; Raghevendra Jayesh; Venkateshwaran; V Dinakarsamy (Wolters Kluwer Medknow Publications, 2015)
Patients with a missing tooth along with diastema have limited treatment options to restore the edentulous space. The use of a conventional fixed partial denture (FPD) to replace the missing tooth may result in too wide anterior teeth leading to poor esthetics. Loss of anterior teeth with existing diastema may result in excess space available for pontic. This condition presents great esthetic challenge for prosthodontist. If implant supported prosthesis is not possible because of inadequate bone support, FPD along with loop connector may be a treatment option to maintain the diastema and provide optimal esthetic restoration. Here, we report a clinical case where FPD along with loop connector was used to achieve esthetic rehabilitation in maxillary anterior region in which midline diastema has been maintained.